Adsorptive solar refrigerators based on composite adsorbents "silica gel - sodium sulphate" - Belyanovskaya, Elena A.; Pustovoy, Grigoriy N.; Sukhyy, Kostyntyn M.; Sergiyenko, Yana O.; Yeromin, Oleksandr O.; Prokopenko, Elena; Gubinsky, Mikhailo V.; Kizek, Ján; Lukáč, Ladislav (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The operation processes of adsorptive solar refrigerators based on composite adsorbents ?silica gel - sodium sulphate? were studied. The correlation between the adsorbent composition and the coefficient of the energy performance of the device was stated. As a consequence of the decreasing of adsorbent mass, the coefficient of performance is increased when sodium sulphate content in the composite increased.
Keywords: adsorptive refrigerator; composite adsorbent; coefficient of performance; adsorptive capacity; regeneration temperature; chłodziarka adsorpcyjna; adsorbent; współczynnik wydajności; zdolność adsorpcyjna; temperatura